TINJAUAN KONDISI FISIK PEMAIN SEPAKBOLA USIA 13-15 TAHUN SSB ESA PRATAMA TAHUN 2025 (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Based on observations of SSB Esa Pratama football players during inter-club matches, it was evident that players experienced fatigue, particularly in the second half. Their movements in the second half often resulted in the ball being easily taken by their opponents. At present, the physical condition of the athletes is unknown. The purpose of this study is to determine the physical condition of 13-15-year-old SSB Esa Pratama football players in 2025. This is a descriptive study, and the sample used in this study is a total population sample because the population size is relatively small, so the entire population of 18 people was used as the sample. Based on the analysis of the 50-metre running fitness test results from 18 people, 8 people were in the good category with a percentage of 44%, 7 people were in the moderate category with a percentage of 39%. Three individuals were classified as poor, representing 17% of the sample. Based on the sit-up fitness test results from the 18 individuals, 8 individuals were classified as good, representing 44% of the sample, while 10 individuals were classified as moderate, representing 56% of the sample. The physical condition of the vertical jump test of 18 people showed that 1 person was in the good category with a percentage of 6%, 15 people were in the moderate category with a percentage of 83%, and 2 people were in the poor category with a percentage of 11%. The physical condition of the Shuttle Run test of 18 people who had a good category was 4 people with a percentage of 22%, who had a moderate category was 12 people with a percentage of 67%, who had a poor category was 2 people with a percentage of 11%. The physical condition of the Sit and Reach test of 18 people showed that 7 people were in the good category with a percentage of 39%, 9 people were in the moderate category with a percentage of 50%, and 2 people were in the poor category with a percentage of 11%. The physical condition of the endurance test with the bleep test of 18 people showed that 1 person was in the good category with a percentage of 6%, 10 people were in the moderate category with a percentage of 56%, and 7 people were in the poor category with a percentage of 39%. The conclusion of this study is that the 13-15-year-old football players of SSB Esa Pratama in 2025 are in the moderate category with a percentage of 56%.